Photoinduced chemistry of biomolecular building blocks and molecules in space - Milesevic, D (2023)
The interactions between light and matter are ubiquitous in the universe and initiate many fundamental chemical processes, such as photosynthesis and vitamin D production. Therefore, gaining a better understanding of how light interacts with molecules and how light-induced reaction mechanisms develop from reactants to products is of great interest.